2019
DOI: 10.1155/2019/9689325
|View full text |Cite
|
Sign up to set email alerts
|

Cynomorium songaricum Extract Alleviates Memory Impairment through Increasing CREB/BDNF via Suppression of p38MAPK/ERK Pathway in Ovariectomized Rats

Abstract: Cynomorium songaricum Rupr is a very important traditional Chinese medicine for tonifying the kidney, which has a significant effect on improving estrogen level on the long term. In many studies, it can improve the learning and memory function of ovariectomized (OVX) model animals. 10 of the 50 rats received only bilateral back surgery and were harvested with the same amount of fat as the ovaries without removing the ovaries as sham group; remains underwent bilateral ovariectomy and equally randomized into fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Ethanolic C. coccineum has an estrogenic RP of 1.78 × 10 –4 ( Zhang et al, 2005 ). Recent studies reported that C. coccineum was antidepressant in perimenopausal rats ( Miao et al, 2017 ) and reduced memory impairment in OVX rats ( Tian et al, 2019 ). In this plant, phytoestrogen- and phytoandrogen-like effects have been detected ( Wang et al, 2017 ; Tao et al, 2019 ) and various type of compounds, including eight triterpenoids, six flavonoids, four fatty acids, eight phenolic acids, one anthraquinone, one nucleoside, and one sterol have been identified ( Li X. et al, 2020 ).…”
Section: Estrogenic Plants For Menopausementioning
confidence: 99%
“…Ethanolic C. coccineum has an estrogenic RP of 1.78 × 10 –4 ( Zhang et al, 2005 ). Recent studies reported that C. coccineum was antidepressant in perimenopausal rats ( Miao et al, 2017 ) and reduced memory impairment in OVX rats ( Tian et al, 2019 ). In this plant, phytoestrogen- and phytoandrogen-like effects have been detected ( Wang et al, 2017 ; Tao et al, 2019 ) and various type of compounds, including eight triterpenoids, six flavonoids, four fatty acids, eight phenolic acids, one anthraquinone, one nucleoside, and one sterol have been identified ( Li X. et al, 2020 ).…”
Section: Estrogenic Plants For Menopausementioning
confidence: 99%
“…Our previous studies have shown that extract of C. songaricum (ECS) has neuroprotective effects in vivo and in vitro. It can alleviate the behavioral changes and morphological damage in animals with AD and resist the cytotoxicity induced by Aβ in vitro [ 26 29 ]. Additionally, by ultrahigh-performance liquid chromatography and mass spectrometry (UPLC/LTQ-Orbitrap MS), we have identified that the main chemical components of ECS are B-type oligomeric forms of flavonoids [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extract of C. songaricum Rupr. displays neuroprotective effects in ovariectomized rats, possibly by p-cAMP-response element binding protein (p-CREB) and brain-derived neurotrophic factor (BDNF) mediating the downregulation of ERK/p38MAPK levels [ 40 ]. Phenolic antioxidants epicatechin and luteolin-7-O- β -D-glucoside extracted from C. songaricum Rupr.…”
Section: Discussionmentioning
confidence: 99%